La femme est une île: Análisis pragmático de los enunciados metafóricos en la publicidad - Alba Reina, Maria José (Verbum – Analecta Neolatina, 2008)
This paper provides an analysis of metaphoric utterances from a Relevance Theoretic point of view. We propose that only a theory which includes the concept of contextual effects is able to explain, in an exhaustive way, how publicity manages to capture the targeted customer’s attention to make them buy the promoted product.